Social Media and the Management of Ethno-Religious Conflicts: Stakeholders’ Perspectives - Sanda, Hajara Umar; Targema, Tordue Simon (The Journal of Society and Media, 2022)
This study examines the utilization of social media to manage ethno-religious conflicts in Taraba State, Nigeria with specific attention to the nature of stories on the platforms on ethno-religious conflicts, how they affect the process of conflict management and the opportunities/threats which the platforms portend to conflict management. Pegged on the Technology Acceptance Model, the study adopts in-depth interview and qualitative content analysis of social media posts as research designs. Population comprises stakeholders engaged in managing ethno-religious conflicts in the state- traditional rulers, religious leaders, leaders of socio-cultural associations and information personnel of security agencies. Eleven respondents have been purposively sampled based on their perceived relevance to conflict management. Facebook posts on conflicts in the state have also been qualitatively analysed to back up the interviews. Findings reveal that social media possess both positive and negative traits in terms of conflict management, and some of the stakeholders utilize them for conflict management while some do not, due largely to their perceptions of the platforms. The study demonstrates that social media have potentials that are vital to conflict management, concomitant with numerous defects, hence, caution must be applied with mitigation strategies adopted while utilizing them to manage conflicts for more impact.